L2 development of phraseological knowledge via a xu-argument based continuation task: A latent curve modeling approach. (June 2022) - Chen, Jianhua; Zhang, Xiaopeng
Abstract: The xu -argument based continuation task is able to closely couple language input with output when learners are continuing or extending an input text. This continuation process has been found to incur alignment to the input text, and consequently promote L2 learning. This article reports on a longitudinal study, testing the effect of a xu -argument based continuation task on Chinese high-school students' English n -gram use over five months via latent growth curve modeling. The unconditional modeling yielded that written bi- and tri-gram proportions and association strength captured by MI and Delta P scores increased for the entire group over time. The conditional modeling showed that the English-English group produced more high-frequency and strongly-associated bi- and tri-grams than the Chinese-English group. These findings substantiate the effectiveness of the xu -argument based continuation task in L2 development of phraseological knowledge and have useful implications for L2 phraseological pedagogy.